1997
DOI: 10.1007/bf02238935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary selenium and vitamin E on the biomechanical properties of rabbit bones

Abstract: It is generally agreed that combined deficiency of selenium and vitamin E leads to several abnormalities including Kashin-Beck disease which is an endemic and chronic degenerative osteoarthrosis. The abnormalities can be reversed by the administration of various forms of selenium and vitamin E. The present study was designed to investigate the effects of dietary selenium and vitamin E on bone tissue and on the biomechanical properties of bone. Young rabbits of both sexes were fed with either a selenium- and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
1
23
0
4
Order By: Relevance
“…The results by Galicka et al (2004) also demonstrate the direct toxic impact of Cd on bone collagen content in rats. Moreover, the decreased biomechanical strength of the femur was also reported in the Se-exposed rabbits (Turan et al 1997). Changes in mechanical properties and composition of bone can be also induced by various OP pesticides as a result of metabolic process disruption of bone tissue (Ware 2001).…”
Section: Discussionmentioning
confidence: 95%
“…The results by Galicka et al (2004) also demonstrate the direct toxic impact of Cd on bone collagen content in rats. Moreover, the decreased biomechanical strength of the femur was also reported in the Se-exposed rabbits (Turan et al 1997). Changes in mechanical properties and composition of bone can be also induced by various OP pesticides as a result of metabolic process disruption of bone tissue (Ware 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In an animal study, bone healing was impaired by the presence of oxygen-free radicals [8]. Antioxidant administration has been shown to be beneficial in suppressing the damaging effects of oxygen-free radicals in cells during bone healing [20,21,26]. Vitamin C deficiency has also been associated with decreased bone density in oxidans in eine orthopädisch geweitete Sutur hat jedoch negative Auswirkungen auf die Knochenbildung.…”
Section: Introductionmentioning
confidence: 99%
“…In einem Tierversuch führte das Vorliegen von freien Sauerstoffradikalen zu einer Behinderung der Knochenheilung [8]. Die Verabreichung von Antioxidantien hat sich als vorteilhaft erwiesen, um die schädlichen Auswirkungen von freien Sauerstoffradikalen in den Zellen während der Knochenheilung zu unterdrücken [20,21,26]. Darüber hinaus wurde Vitamin-C-Mangel in Tierversuchen auch mit einer geringeren Knochendichte in Verbindung gebracht [1,12,20].…”
Section: Introductionunclassified
“…16 Findings from animal studies indicate that α-tocopherol improves calcium content and mechanical properties of bone tissue. 17,18 Moreover, the USA Food and Drug Administration (FDA) classify α-tocopherol as Generally Recognized as Safe (GRAS) and it is worldwide approved for use in foods contact applications. Moreover, there are new studies that have shown the beneficial effects of α-tocopherol on bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are new studies that have shown the beneficial effects of α-tocopherol on bone formation. [9][10][11]17,18 Effects of α-tocopherol on long bone distraction osteogenesis (DO) also have been investigated. Therefore, to our best notice, our study is the first report to evaluate the effects of α-tocopherol on bone formation in the sutural area.…”
Section: Introductionmentioning
confidence: 99%